Review on physical properties and acrylamide formation in seaweed bread - Aabel, Lukas Salvó; Jensen, Sarah Normann; Hakme, Elena; Feyissa, Aberham Hailu (Frontiers in Food Science and Technology, 2023)
Bread, a dietary staple worldwide, owes its diverse physical properties to a complex interplay of composition and processing. This review focuses on recent developments in understanding the physical attributes of bread. It particularly emphasises the effects of ingredient substitution with seaweed, processing parameters, and acrylamide formation. It also encompasses aspects, such as kinetic studies. Special attention is given to the integration of seaweed in bread production. Additionally, it addresses the challenges faced in this field and offers prospects for future research.